A genetic approach to improvements of Candida tropicalis as a biocatalyst - Perry, Patricia Mair (Cranfield University, 1990)
It is well documented in the literature that, in addition to carbon sources such as glucose, Candida species are able to utilise a wide variety of n-alkanes which are degraded via beta-oxidation. Prior to beta-oxidation a primary oxidation system acts on the end terminal methyl groups to generate carboxyl groups. The main industrial aim of the work was to optimise the bioconversion of pelargonate [CH3(CH2)7COOH] to azeleate [HOOC(CH2)7COOH], i.e. the primary oxidation steps, by blocking the beta-oxidation pathway in C. tropicalis. To this end, a library of Sau 3AI partially digested C. tropicalis NCYC997 genomic DNA in pBR322 was constructed from which it was hoped to isolate and disrupt the long-chain fatty acid acyl-CoA oxidase genes, POX4 and POX5, which catalyse the first step of beta-oxidation. The library was probed with oligonucleotides specific to POX4 and POX5, and a putative POX4 clone was isolated.